ADAPTATIVE EVOLUTION OF THE HEAT SHOCK RESPONSE IN ANTARCTIC CILIATES - PASSINI, Valerio (Università degli Studi di Camerino, 2007)
During my PhD, the general objective of my work was to contribute to a better knowledge of the molecular basis of Heat Shock Response in eukaryotic microorganisms. In particular, I was interested in analyzing the plasticity of hsp70 gene expression in marine species of ciliates inhabiting the cold and thermally stable coastal sea water of Antarctica. Useful organism models for analysis of adaptation of gene expression were represented by two Antarctic species of Euplotes, E. focardii andE. nobilii, which showed up marked differences in their capacity to activate hsp70 gene expression in response to thermal insults. The specific aims of my PhD projects were: 1. To perform a comparative analysis of hsp70 gene structures (at level of coding and non-coding, regulatory regions) between the two Antarctic species of Euplotes, E. focardii and E. nobilii, with the ultimate goal to identify the causes of the unresponsiveness to thermal stress in E. focardi. (Chapter 1) 2. To perform a comparative analysis of hsp70 gene structures (at level of coding and non coding, regulatory regions) and a preliminary examination of the DNA-binding activity of Heat Shock Factors by means of Electrophoretic Mobility Shift Assay approaches in E. nobili and E. raikovi a species inhabiting temperate waters and thus, adapted to a fluctuating thermal environment. The possibility to compare the transcriptional machinery of closely related species adapted to different thermal regimes, might provide valuable clues for unraveling the molecular mechanisms of transcription in the cold. (Chapter 2)